The effect of interpreting experience on self-monitoring in translation processes - Pavlović, Nataša (Array, 2011)
Some evidence from process research (see Tirkkonen-Condit 2005) suggests that Ivir (1981) might have been right in asserting that translators begin their search for the best translation with “formal correspondence” (FC), and look for alternative solutions only when this default version is found lacking (Shlesinger & Malkiel 2005, Jakobsen, Jensen & Mees 2007 ; Englund Dimitrova 2005). On the other hand, the very influential concept of deverbalization (Seleskovitch, Lederer, Dejean le Féal, Gile) seems to suggest that interpreters and translators can be trained to behave differently, in a way which considerably limits the role of formal correspondence in the decision-making process. In this study we have decided to approach the “formal correspondence default” from a slightly different angle, and to test whether it is affected by the translator’s extensive deverbalization experience. We want to see what will happen with literal (cognate, FC) solutions if translators who are also interpreters, and who have been exposed to the deverbalization method in the course of their training, are asked to translate the same text as professional translators with no such experience. We might expect that the training/experience in interpreting will have an effect on the translation process, resulting in fewer literal solutions being captured by the keystroke logging program Translog as the default (initial) solution in the logs of interpreters/translators than in those of the other group. Should that be the case, further stages of the self-revision process might also exhibit some interesting differences, most obviously in what we call “distance dynamics”. The latter concept refers to possible patterns in the order of translation solutions with respect to their closeness to the source-text form. The two groups of subjects – interpreters/translators, and translators with no interpreting experience – will be asked to translate the same general-language text from their L2 or B-language (English) into their L1 or A-language (Croatian). Both groups will be asked to work under time pressure, as this is expected to reduce the degree of inevitable (and unrecordable) self-revision before the default solutions have had a chance to be recorded in the logs. The data will be analyzed in terms of total number of cognate solutions appearing in the logs of each group, and also in terms of “distance dynamics”. Our earlier research suggests the latter might be related to individual translation style, which may or may not prove to correlate with training in the deverbalization method.